The Path to Reconciliation: Understanding the Hiraago Cultural Peacemaking Social Philosophy of the Hadiya, Ethiopia - Onsamo, Daniel Handino; Musalaiah, Jadi (South Asian Journal of Social Sciences and Humanities, 2024)
This article investigates “Hiraago” peacemaking practices in the Hadiya Social Philosophy,  Ethiopia. The main goal of the study is to examine how the “Hiraago” practice aids in the  resolution of disputes and the promotion of reconciliation and social cohesion among the  Hadiya. Both primary and secondary data were utilized. The data was collected through in depth interviews and observation. Other techniques of gathering information included  analyzing articles from cultural magazines and journals. The “Hiraago” practice, which is  strongly entrenched in the Hadiya tradition, is demonstrated to resolve complex, concealed,  and long-standing issues and foster peaceful coexistence. The study indicates that “Hiraago” is important peacemaking methods that influence human relations and promotes  reconciliation and forgiveness among conflict parties, hence contributing to the maintenance  of peace in the studied area. The study suggests more research into the “Hiraago” and other  indigenous model peacemaking techniques in social Philosophy of the Hadiya and other  community traditional practices. And it urges collaboration between traditional peacemaking  methods and modern ones to improve conflict resolution and peace sustainability.
Keywords: Cultural; Ethiopia; Hadiya; Hiraago; Peacemaking